Transient Analysis of Pump-induced Lensing Effects in Alexandrite Lasers Using Pump-Probe Technique - Jiang Xunuo; Xiao Huaifeng; Damzen Michael J. (EPJ Web of Conferences)
A novel transient pump-probe method is used to differentiate thermal and population pump-induced lensing mechanisms. In diode-pumped Alexandrite lasers, excellent agreement is found between theory and experiment and the population lens is found to be dominant in non-lasing amplifier.